Origin of Boron and Brine Evolution in Saline Springs in the Nangqen Basin, Southern Tibetan Plateau - Ji-long Han; Feng-qing Han; Syed-Asim Hussain; Wen-yu Liu; Xiu-qing Nian; Qing-fei Mao (Geofluids)
The Nangqen Basin is a typical shearing-extensional basin situated in the hinterland of the Tibetan Plateau. It contains abundant saline spring resources and abnormal trace element enrichments. The hydrochemical molar ratios (Na/Cl, B/Cl, and Br/Cl), H-O isotopes, and B isotopes of the saline spring were systematically measured to describe the evolution of brines and the origin of the boron. The sodium chloride coefficient of the water samples in this area is around 1.0 or slightly greater, which is characteristic of leached brines; the highest B/Cl value is 4.25 (greater than that of seawater). The Na/Cl, B/Cl, and Br/Cl values of the springs are clear indicators of a crustal origin. The δ18O values of the spring waters range from −12.88‰ to −16.05‰, and the δD values range from −100.91‰ to −132.98‰. Meanwhile the B content and B isotopes in the saline springs are in the ranges of 1.00 to 575.56 ppm and +3.55‰ to +29.59‰, respectively. It has been proven that the saline springs in the Nangqen Basin are a type of leached brine, suggesting that the saline springs have a terrestrial origin. The δ11B-B characteristics of the springs are similar to those observed in the Tibetan geothermal area, indicating that these two places have the same B source. Moreover, they have a crustal origin (marine carbonate rocks and volcanic rocks) instead of a deep mantle source.